Correlation Between The Rate of Self Confidence to Teenagers Aggression Behavior in Grade XI at SMA Dwijendra Denpasar. - Kusumadewi, A.A. Sagung Istri (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
Adolescence is a time of physical, cognitive, emotional, and social development rapidly. Some teens seem to have good self confidence so as to reduce the problem without excessive anxiety. Lack of confidence can lead teens can’t solve a complex problem that does some teenage aggression aimed at protecting the weakness itself. This study aims to determine the correlation of self confidence with teenagers’ aggression behavior. The study used Descriptive Correlational method with Cross Sectional approach. The sample consisted of 205 teenagers and used Simple Random Sampling . Questionnaire is used to collect the data. The result of the analysis shown that the respondents who had non-aggression behaviors were those who had high self confidence and average self confidence by the percentage of  38,54% (79 sample) and 31,71% (65 sample), whereas the respondents who shown aggression behavior were mostly found in those who had low self confidence, which consist of 37 sample (18,05%). Based on the correlation test results of coefficient contingency, it was found that p value is 0.000 (p <0.05) and X² value (98,023) > X² table (3,481) which means that Ha is accepted, it means there is a significant correlation between self confidence with teenagers’ aggression behavior and it was represented by the value of 0,569 or 56,9% based on the C value (Coefficient Contingency). Based on this study finding, it is suggested to the school to keep developing the counseling and guiding programs comprehensively related to educational psychology. Caregivers of teenagers should give an education to teenagers related to self confidence and aggression behavior problems.
Keywords: Self Confidence, Aggression behavior, Teenagers